Inmediate presidential reelection and democracy movement in colombia (2006)
This article examines the dynamics of the democratic participation within the framework of presidential succession under the government of Álvaro Uribe Vélez, from the system theory’s point of view. Therefore, as a resource of government reform, the reelection restructures the Colombian presidentialism defined in the Constitution of 1991 both socially and politically, as opposed with the effective application of constituent power. The historically incipient governability and security are the practices used by the government as a strategic decision in this particular regime to subdue the majority; which results in social war. The social aspect acquires political value, and this is not reflected in a traditional way, as it was within the State and as it is stated by the government. The political system itself reveals the social nature of the relation government-governees, who have been thought of as multitudes since Negri-Hardt and who are no longer willing to let their representatives decide for them. The last elections’ results prove this opposing process: a national reactionary tendency that is contrasting due to electoral advance as well as non-electoral advance of the democratic, liberal and left-wing forces; pleading for a change in the model of capitalistic accumulation which favors the democratic security regime.